Novel endothelial cell-specific AQP1 knockout mice confirm the crucial role of endothelial AQP1 in ultrafiltration during peritoneal dialysis - Zhang, Wei; Freichel, Marc; Hoeven, Frank van der; Nawroth, Peter Paul; Katus, Hugo; Kälble, Florian; Zitron, Edgar; Schwenger, Vedat (PLOS ONE, 2016)
The water channel aquaporin-1 (AQP1) mediates about 50% ultrafiltration during a 2-hour hypertonic dwell in global AQP1 knockout (AQP1-/-) mice. Although AQP1 is widely expressed in various cell types including mesothelial cells, the ultrafiltration has been assumed to be mediated via endothelial AQP1 of the peritoneum. The partial embryonic lethality and reduced body weight in AQP1-/- mice may reflect potential confounding phenotypic effects evoked by ubiquitous AQP1 deletion, which may interfere with functional analysis of endothelial AQP1. Using a Cre/loxP approach, we generated and characterised endothelial cell- and time-specific AQP1 knockout (AQP1fl/fl; Cdh5-Cre+) mice. Compared to controls, AQP1fl/fl; Cdh5-Cre+ mice showed no difference in an initial clinical and biological analysis at baseline, including body weight and survival. During a 1-hour 3.86% mini-peritoneal equilibration test (mini-PET), AQP1fl/fl; Cdh5-Cre+ mice exhibited strongly decreased indices for AQP1-related transcellular water transport (43.0% in net ultrafiltration, 93.0% in sodium sieving and 57.9% in free water transport) compared to controls. The transport rates for small solutes of urea and glucose were not significantly altered. Our data provide the first direct experimental evidence for the functional relevance of endothelial AQP1 to the fluid transport in peritoneal dialysis and thereby further validate essential predictions of the three-pore model of peritoneal transport.